2006
DOI: 10.1177/154193120605002501
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Performance and Cognitive Efficiency when Training for X-Ray Security Screening

Abstract: We describe an experiment designed to understand the X-ray security screener task via investigation of how training environment and content influence perceptual learning. We examined both perceptual discrimination and the presence/absence of clutter during training and how this impacted performance. Overall, the data show that performance was generally better when there were clutter items in the training images. We also examined the diagnosticity of a measure of cognitive efficiency, a combinatory metric that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…Required mental resources were quantified using normalized-and-scaled measures of subjective mental workload (NASA-TLX) and physiological measures according to Equation 5. In instructional efficiency research, workload assessments have almost exclusively used retrospective subjective ratings (Fiore et al, 2006; Paas et al, 2003; Paas & van Merriënboer, 1993), which are appropriate for the longer time intervals involved in long-term memory encoding and skill development. In contrast, our interests concern short intervals, working memory processing, immediate application of task-relevant information, and continuous activity that ideally is not disrupted by workload surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Required mental resources were quantified using normalized-and-scaled measures of subjective mental workload (NASA-TLX) and physiological measures according to Equation 5. In instructional efficiency research, workload assessments have almost exclusively used retrospective subjective ratings (Fiore et al, 2006; Paas et al, 2003; Paas & van Merriënboer, 1993), which are appropriate for the longer time intervals involved in long-term memory encoding and skill development. In contrast, our interests concern short intervals, working memory processing, immediate application of task-relevant information, and continuous activity that ideally is not disrupted by workload surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Educational psychologists have measured the “instructional efficiency” of teaching materials and methods by quantifying students’ performance (usually with test scores) and imposed mental workload during learning via subjective ratings (e.g., Kalyuga & Sweller, 2005; Paas, Tuovinen, Tabbers, & Van Gerven, 2003; Paas & van Merriënboer, 1993; van Gog & Paas, 2008). Similar methods have also been used to evaluate the efficiencies of various training programs (Fiore, Scielzo, Jentsch, & Howard, 2006; Salden, Paas, Broers, & van Merriënboer, 2004) and information portals, such as websites (lo Storto, 2013). Whereas these efforts measure effectiveness in terms of memory encoding (i.e., learning), the current research concerns processing of displayed information to support real-time performance in multiple ongoing tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Content complexity can be increased through the use of non-threat distracter items that are similar in appearance to threat items. The literature on skill acquisition (e.g., Alderton, Cross, & Doane, 2002;Doane, Alderton, Sohn, & Pellegrino, 1996;Doane, Sohn, & Schreiber, 1999;Sohn, Doane, & Garrison, 2006) describes increases in perceptual learning through manipulation of the degree of similarity between the threat items (Fiore, Scielzo, Jentsch, & Howard, 2006). However, in exposure-based training, there is no opportunity to discriminate between threats, and the required interrogation of images is minimal.…”
Section: Training Complexitymentioning
confidence: 99%
“…First, we will discuss how IEDs are an example of an immediate new threat that necessitates innovative training methods. Second, we explore how recent advances, moving threat detection training beyond exposure training (Fiore, Scielzo, Jentsch, & Howard, 2006), can be augmented with methods derived through adaptive testing theory. In particular, we propose two training interventions where potentially complementary training technologies are combined: individually adaptive exposure training and individually adaptive discrimination training.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to decision making on whether a bag contains a prohibited item, screeners need to know which items are prohibited and what they look like in X-ray images (Schwaninger, 2005). Several studies have shown the importance of computer-based training in helping screeners to achieve and maintain high visual inspection performance (Fiore, Scielzo, Jentsch, & Howard, 2006;Halbherr, Schwaninger, Budgell, & Wales, 2013;Koller et al, 2009;Koller, Hardmeier, Michel, & Schwaninger, 2008;Schuster, Rivera, Sellers, Fiore, & Jentsch, 2013;Schwaninger & Hofer, 2004;Schwaninger, Hofer, & Wetter, 2007). International regulations take this into account by mandating initial and recurrent training of screeners.…”
mentioning
confidence: 99%